Comment on “A Comparative Study of Narrative Thought in Chinese and Western Classical Literature” - Zhang, Yijun (2025)
Commented article: CHEN, M. A comparative evaluation of the narrative thoughts in Chinese and Western classical literature. Trans/Form/Ação: revista de filosofia da Unesp, v. 47, n. 5, e02400135, p. 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15070.